Calibration of Electrocardiograph (ECG) Simulators. Issue 1 (3rd April 2018) - Yang, Steven; Lam, Brenda; Ng, Chris M. N.
Abstract: The Standards and Calibration Laboratory (SCL) in Hong Kong has set up a calibration facility for electrocardiograph (ECG) simulators. ECGs are medical devices designed to measure the electrical signals associated with cardiac activities. They are used to diagnose heart diseases and arrhythmias, and are commonly used in hospitals, emergency facilities, and medical institutes. Routine performance check of ECGs could be performed by ECG simulators. To ensure the accuracy of ECGs, traceable calibration to SI units is essential. At the SCL, the output signal from an ECG simulator is measured by a differential amplifier and a high-speed digital sampling system. The digital sampling system enables the calibration of non-sinusoidal signal with high accuracy. Signal characteristics including signal amplitude, frequency, and wave shape could be evaluated by an in-house developed program for normal sinus rhythm waveforms as well as for performance waveforms.